(untitled) (2025)
Research This research aims to improve the learning outcomes of Indonesian content in grade IV of SDN Karanganyar Gunung 02 through the application of the Problem Based Learning (PBL) model assisted by Student Worksheets (LKPD). This Class Action Research is carried out in 2 cycles, namely pre-cycle, sklus I and cycle II, two cycles with stages of planning, implementation, observation, and reflection in each cycle. The subject of this study is the students of grade IV of SDN Karanganyar Gunung 02 with a total of 25 students. The data collection techniques in this study are by test, observation and documentation techniques. Data analysis technique uses quantitative descriptive analysis techniques The results of the study show that the application of the LKPD-assisted PBL model can improve students’ Indonesian learning outcomes. In the pre-cycle, the average student learning outcome was 71.16 with classical completeness of 40%. In the first cycle, the average student learning outcome increased to 73 with 72% completeness. In cycle II, the average student learning outcome increased to 82.1 with classical completeness of 91.7%. This shows that the application of the LKPD-assisted PBL model can improve the learning outcomes of Indonesian content of grade IV students of SDN Karanganyar Gunung 02